UNITED STATES STRATEGY AND AFGHAN NATIONAL SECURITY - DARKHOR, Mohammad; KAFI, Saeed; Hadi SADATI, Seyed (CENTRAL ASIA AND THE CAUCASUS, 2013)
The United States attacked Afghanistan in October 2001, beginning the longest war in American history. Ten years later, on 22 June 2011, Barack Obama announced that the United States would pull American troops out of Afghanistan. While there is a failed government with instability in Afghanistan, the Taliban will remain powerful, carrying out criminal actions against the Afghan people and coalition forces. After the withdrawal of American troops, Afghanistan will pose both challenges and opportunities in the region, but this will depend on America’s crisis management in the region. This article analyzes the new situation in Afghanistan after the withdrawal of U.S. troops and the impact the New Obama Strategy will have on Afghanistan’s national security. This research adopts a descriptive-analytic approach, using books and scholarly articles published in different scientific journals, as well as interviews from government sources and official news agencies.